Payers' Views of the Changes Arising through the Possible Adoption of Adaptive Pathways - Ermisch, Michael; Bucsics, Anna; Vella Bonanno, Patricia; Arickx, Francis; Bybau, Alexander; Bochenek, Tomasz; van de Casteele, Marc; Diogene, Eduardo; Fürst, Jurij; Garuolienė, Kristina; van der Graaff, Martin; Gulbinovič, Jolanta; et al. (Frontiers in Pharmacology, 2016)
Payers are a major stakeholder in any considerations and initiatives concerning adaptive licensing of new medicinal products, also referred to as Medicines Adaptive Pathways to patients (MAPPs). Firstly, the scope and necessity of MAPPs need further scrutiny, especially with regard to the definition of unmet need. Conditional approval pathways already exist for new medicines for seriously debilitating or life-threatening diseases and only a limited number of new medicines are innovative. MAPPs will result in new medicines initially with limited evidence about their effectiveness and safety. Additional data are to be collected after approval. Consequently, adaptive pathways may increase the risk of exposing patients to ineffective or unsafe medicines. We have already seen medicines approved conventionally that subsequently proved ineffective or unsafe amongst a wider, more co-morbid population as well as medicines considered for approval under MAPPs but subsequently proved ineffective or unsafe in Phase III trials and were never licensed. MAPPs also put high demands on payers. Routine collection of patient level data is difficult with high transaction costs. It is not clear who will fund these. Other challenges for payers include shifts in the risk governance framework, implications for evaluation and HTA, increased complexity of setting prices, difficulty with ensuring equity in allocation of resources, liability and implementation of stratified use, Exit strategies also need to be agreed in advance, including price reductions, rebates or reimbursement withdrawals when price premiums are not justified. These issues and concerns will be discussed in detail including potential ways forward.